PUBLIC EDUCATION AT THE DAWN OF THE NEW MILLENNIUM: THE NEW ZEALAND EXPERIMENT - Haché, Denis (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1999)
ABSTRACT. Globalization and the introduction of new information technologies are producing changes and upheavals felt by all segments of society. Public education is being shaken by these shock waves and confronted by public skepticism and media criticism as well as strong demands for systemic and curriculum reform. Proponents of a corporate model in education argue that parental choice and the concept of competition within the school system are the only viable solutions to the present ills of public education. New structural organizations are being proposed such as charter schools, school councils, total quality schools (TQM) and many other variations of the same type, in other words, the creation of "The Industry of Education" as often mentioned by corporate reformists. New Zealand represents a typical example of such an endeavor and illustrates very well the drastic changes provoked by restructuring in the personal and professional life of all stakeholders, where consumer and corporate interests are sometimes in conflict with citizen rights and public good. RÉSUMÉ. La mondialisation et l'adoption de nouvelles technologies de l'information entrainent des changements et des bouleversements qui sont ressentis par tous les segments de la société. L'éducation publique subit les contrecoups de ces bouleversements et doit affronter le scepticisme du public et la critique des médias et répondre à ceux qui exigent une réforme du système et des programmes. Les tenants d'un modèle corporatif en éducation soutiennent que le choix des parents et la notion de compétition au sein du réseau scolaire sont les seules solutions viables aux maux actuels de l'éducation publique. De nouveaux types de structures sont proposés comme les écoles à charte, les conseils scolaires, les écoles de qualité totale (OOT) et bien d'autres variations sur le même type, en d'autres termes, la création de "l'industrie de l'éducation" comme l'appellent souvent les réformistes. La Nouvelle-Zélande est un exemple typique d'un tel effort qui illustre fort bien les changements draconiens provoqués par la restructuration de la vie personnelle et professionnelle de tous les intervenants où le consommateur et les intérêts commerciaux entrent parfois en conflit avec les droits des citoyens et l'intérêt public.